Optimized Silicon QPSK Modulator With 64-Gb/s Modulation Speed - Haike Zhu; Linjie Zhou; Tao Wang; Lei Liu; Chiyan Wong; Yanyang Zhou; Rui Yang; Xinwan Li; Jianping Chen (IEEE Photonics Journal, 2015)
We demonstrate a compact silicon quadrature phase-shift keying (QPSK) modulator consisting of two nested Mach-Zehnder interferometers with a size of 4.5-mm2. The V11 · L of the modulator is 1.4 V · cm with an insertion loss of 8 dB. In addition, 64-Gb/s QPSK modulation is achieved with an error vector magnitude (EVM) of 24.4% and bit error rate (BER) of 2.1 × 10-5 at the received optical power of -10 dBm after the device and an EVM of 31.7% and BER of 8.4 × 10-4 at the received optical power of 0 dBm after 10-km single-mode fiber transmission. The estimated power consumption is 7.1 pJ/bit for the 64-Gb/s QPSK modulation.